Association between glycemic control and serum fibrinogen levels in type 2 diabetes mellitus patients - Topiwala, Moiz; Bahulikar, Arun; Beke, Nandkumar; Khadke, Vrushali; Phalgune, Deepak (International Journal of Advances in Medicine, 2019)
Background: Poor glycemic control has been reported to be associated with increased vascular complications in diabetes mellitus (DM) patients. High fibrinogen level has been described as an independent risk factor for cardiovascular diseases. High fibrinogen has been suggested to be involved in the excess rate of cardiovascular diseases in patients with type 2 DM. The present study was undertaken to find correlation between glycemic control and plasma fibrinogen level in patients with type 2 DM. Methods: Three hundred ten patients aged ≥30 years of either sex were included in this cross sectional study. Estimation of glycated haemoglobin (HbA1c), serum fibrinogen, serum total cholesterol (TC), serum triglycerides (TG), serum high density lipoprotein (HDL) cholesterol, and serum low density lipoprotein (LDL) cholesterol was done. Categorical and continuous variables were tested using Chi-Square test/Fisher’s exact test and unpaired ‘t’ test respectively. Pearson’s correlation was used to study correlation between serum fibrinogen levels and HbA1c, Body mass index (BMI), TC, LDL cholesterol, HDL cholesterol, and TG. Results: Mean serum fibrinogen levels were significantly higher in DM patients whose HbA1c, LDL cholesterol and TG levels were higher. Correlation between serum fibrinogen was 0.59, and 0.45 with HbA1c, and BMI respectively. Multivariate step-wise regression analysis showed higher HbA1c and higher BMI were the independent and significant predictors of higher serum fibrinogen levels. HbA1c was the stronger predictor of serum fibrinogen than BMI. Conclusions: Fibrinogen levels were independently associated with HbA1c value in patients with type 2 DM.